COMPARATIVE ANALYSIS OF RISK FACTORS FOR STROKE AMONG NATIVE PEOPLES REPUBLIC OF TYVA - B. M. Doronin; Kh. D. Mongush; A. B. Ondar; R. Ch. Chylbak-ool (Бюллетень сибирской медицины)
Objective: a comparative analysis of risk factors for stroke in patients with stroke, depending on sex, analysis of the frequency of occurrence of risk factors in patients and healthy people Tuvan nationality. Materials and methods. A case-control study of major risk factors for ischemic stroke (hypertension, family history, cardiac pathology, diabetes, etc.) in the two groups. Results. The first place is in the frequency of hypertension, family history and then, at the last-myocardial infarction. Conclusions. Among the population of Tuva has been a clear upward trend in ischemic stroke associated primarily with a high prevalence of hypertension, inadequacy of its treatment, as well as alcohol abuse.